CircHYBID regulates hyaluronan metabolism in chondrocytes via hsa-miR-29b-3p/TGF-β1 axis - Hong-Xing Liao; Zhi-Hui Zhang; Hui-Lin Chen; Ying-Mei Huang; Zhan-Liang Liu; Jian Huang (BMC, 2021)
Abstract Background Hyaluronan (HA) metabolism by chondrocytes is important for cartilage development and homeostasis. However, information about the function of circular RNAs (circRNAs) in HA metabolism is limited. We therefore profiled the role of the novel HA-related circRNA circHYBID in the progression of osteoarthritis (OA). Methods CircHYBID function in HA metabolism in chondrocytes was investigated using gain-of-function experiments, and circHYBID mechanism was confirmed via bioinformatics analysis and luciferase assays. The expression of circHYBID-hsa-miR-29b-3p-transforming growth factor (TGF)-β1 axis was examined by quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting. CircHYBID, TGF-β1, and HA levels in cartilage samples were evaluated using qRT-PCR and pathological examination. Enzyme-linked immunosorbent assay was used to assess HA accumulation in chondrocyte supernatant. Results CircHYBID expression was significantly downregulated in damaged cartilage samples compared with that in the corresponding intact cartilage samples. CircHYBID expression was positively correlated with alcian blue score. Interleukin-1β stimulation in chondrocytes downregulated circHYBID expression and decreased HA accumulation. Gain-of-function experiments revealed that circHYBID overexpression in chondrocytes increased HA accumulation by regulating HA synthase 2 and HYBID expression. Further mechanism analysis showed that circHYBID upregulated TGF-β1 expression by sponging hsa-miR-29b-3p. Conclusions Our results describe a novel HA-related circRNA that could promote HA synthesis and accumulation. The circHYBID-hsa-miR-29b-3p-TGF-β1 axis may play a powerful regulatory role in HA metabolism and OA progression. Thus, these findings will provide new perspectives for studies on OA pathogenesis, and circHYBID may serve as a potential target for OA therapy.